Dynamics of extracellular superoxide production by Trichodesmium colonies from the Sargasso Sea. (12th May 2016) - Hansel, C. M.; Buchwald, C.; Diaz,, J. M.; Ossolinski, J. E.; Dyhrman, S. T.; Van Mooy, B. A. S.; Polyviou, Despo
Abstract: Reactive oxygen species (ROS) are key players in the health and biogeochemistry of the ocean and its inhabitants. The vital contribution of microorganisms to marine ROS levels, particularly superoxide, has only recently come to light, and thus the specific biological sources and pathways involved in ROS production are largely unknown. To better understand the biogenic controls on ROS levels in tropical oligotrophic systems, we determined rates of superoxide production under various conditions by natural populations of the nitrogen‐fixing diazotroph Trichodesmium obtained from various surface waters in the Sargasso Sea. Trichodesmium colonies collected from eight different stations all produced extracellular superoxide at high rates in both the dark and light. Colony density and light had a variable impact on extracellular superoxide production depending on the morphology of the Trichodesmium colonies. Raft morphotypes showed a rapid increase in superoxide production in response to even low levels of light, which was not observed for puff colonies. In contrast, superoxide production rates per colony decreased with increasing colony density for puff morphotypes but not for rafts. These findings point to Trichodesmium as a likely key source of ROS to the surface oligotrophic ocean. The physiological and/or ecological factors underpinning morphology‐dependent controls on superoxide production need to be unveiled to better understand and predict superoxide production by Trichodesmium and ROS dynamics within marine systems.